2016
DOI: 10.1159/000444266
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in a Series of Dystonia Patients Treated with Deep Brain Stimulation: Outcomes and Management Recommendations

Abstract: Background: Medically refractory dystonia affects children and young adults, and deep brain stimulation (DBS) can allow some patients to regain functional independence. Women with dystonia treated with DBS may wish to conceive a child, but there is limited published information on pregnancy and DBS. Objective: To describe a series of dystonia patients treated with DBS who later became pregnant and provide guidelines for women treated with DBS considering conception. Methods: We reviewed all dystonia DBS cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
(16 reference statements)
0
20
0
1
Order By: Relevance
“…Supplementary Table S1 and Table summarize the publications reviewed and outcomes, respectively . In brief, 31 publications reported the use of levodopa in 148 pregnancies, with examples of reported adverse outcomes including congenital malformation (n = 8) and seizures .…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table S1 and Table summarize the publications reviewed and outcomes, respectively . In brief, 31 publications reported the use of levodopa in 148 pregnancies, with examples of reported adverse outcomes including congenital malformation (n = 8) and seizures .…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, some had a problem-free pregnancy. [ 5 6 ] None of the studies provided details about the charging processes during pregnancy. There was no change in the baby's movements or heart rate during charging periods in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…reported that only three of seven patients experienced worsening of dystonia symptoms during pregnancy, and these symptoms resolved within 3 months after birth. [ 6 ] Two of these patients were diagnosed with isolated segmental dystonia, while the third was diagnosed with isolated hemidystonia. Meanwhile, in the study of Paluzzi et al ., none of the pregnant patients ( n = 3) experienced worsening of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations